A Transcendental Unbounded Continued Fraction Expansions over A Finite Field - Ghorbel, Rima; Kthiri, Hassen (Journal of the Indonesian Mathematical Society, 2021)
Let Fq be a finite field and Fq((Xâˆ’1 )) the field of formal power series with coefficients in Fq. The purpose of this paper is to exhibit a family of transcendental continued fractions of formal power series over a finite field through some specific irregularities of its partial quotients